PENDIDIKAN BERBASIS KARAKTER BAGI PARA GURU PONDOK PESANTREN YAYASAN MUJAHIDIN DI KABUPATEN MALANG - Alifiulahtin Utaminingsih; Rizqi Bachtiar (Publisher UPT P2M Politeknik Negeri Malang, 2019)
Character education is internalization process of moral values for improve to develop skill, morality, emotional and human skill. National Education Program to built Indonesian people’s have skill and competitiveness with justice, quality and relevance with world globally. Based Policy to reach these mission is there is awareness that nation competitiveness only can reach holistic quotition, such as; intelectual, spritual, emotional and social quotition. Based on this trainning want to give solution about learning method and learning media to teachers with characterize based that good can be reached by student in Boarding Shool of Mujahidin of Malang District.